2013
DOI: 10.9790/1684-0627276
|View full text |Cite
|
Sign up to set email alerts
|

Application of Domino Theory to Justify and Prevent Accident Occurance in Construction Sites

Abstract: since the construction activities involve most complex processes and the most intensive administrative atmosphere as well, the accident events come raised in different situations and due to various causations. Most of the construction accidents originate from human errors and operation sources such as equipments and facilities in work processes. Most accidents lead to the loss of life, injuries and loss of properties. The other possible results due to the errors, unsafe acts, and unsafe conditions can be categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…, 2014). Rad (2013) found that 88% of accidents were caused by an unsafe act, 10% by unsafe conditions, and 2% by what they called acts of God. As the crucial role of workers' behavior in the accident causation models attracts much attention (Mohammadfam et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2014). Rad (2013) found that 88% of accidents were caused by an unsafe act, 10% by unsafe conditions, and 2% by what they called acts of God. As the crucial role of workers' behavior in the accident causation models attracts much attention (Mohammadfam et al.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to do so is known to primarily stem from their unsafe behavior (Park et al, 2017), although secondary causes like shortcomings in the design, defective tools, improper procedures or negligent management might also be involved (Shin et al, 2014). Rad (2013) found that 88% of accidents were caused by an unsafe act, 10% by unsafe conditions, and 2% by what they called acts of God. As the crucial role of workers' behavior in the accident causation models attracts much attention (Mohammadfam et al, 2017), behavioral methods, such as behavior-based safety (BBS), evolve to raise workers' safety behavioral performance (Choi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Heinrich Domino theory explained the accident causations in five metaphorical dominoes in preventing accidents. Later, Heinrich theory was updated by Bird and Loftus analyzing the sequences and with the addition of new dominoes (Sabet, 2013). Hence, the domino principle can be used for any sequence of events by understanding its depth, as every event has its cause and consequence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heinrich Domino theory explained the accident causations in five metaphorical dominoes in preventing accidents. Later, Heinrich theory was updated by Bird and Loftus analyzing the sequences and with the addition of new dominoes (Sabet, 2013).…”
Section: Domino Principle In Various Contextsmentioning
confidence: 99%
“…Bu hataların en önemlilerinden biri de dikkat eksikliğidir. Özellikle denetim tabanlı işlerde görsel dikkat, işin başarısı adına hayati önem teşkil etmektedir (Sabet ve Ghasemi, 2013).…”
Section: Introductionunclassified